Casein precipitation by acid and rennet coagulation of buttermilk: Impact of pH and temperature on the isolation of milk fat globule membrane proteins. (December 2016) - Holzmüller, Wolfgang; Gmach, Oliver; Griebel, Anna; Kulozik, Ulrich
Abstract: Milk fat globule membrane (MFGM) proteins make up only 2–3% of the total protein content in buttermilk. Prior isolation of buttermilk MFGM material is therefore required for further investigation of its functional properties and application in food systems. Rennet induced coagulation has been applied to remove caseins, but 30–70% of MFGM proteins are entrapped in the casein curd under classical cheese making conditions. Therefore, factors influencing the rennet as well as acid induced coagulation of buttermilk with regard to a reduction of MFGM protein losses into the casein curd, i.e., pH, temperature and pre-heat treatment of buttermilk, were examined. Complete casein removal from buttermilk was reached using both coagulation methods, whereas retention of MFGM proteins in the serum phase was higher during renneting. Rennet induced coagulation at higher pH and lower temperatures resulted in weaker gel structures, which increased the yield of MFGM proteins in the buttermilk whey.